Proper D - Lucky Labeling on Arbitrary Super Subdivision of New Family of Graphs - Esakkiammal, E; Thirusangu, K; Seethalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we prove the existence of proper d – lucky labeling of the arbitrary super subdivision of some new family of graphs (〖 P〗_(m ) ∶ Q_3 )and [〖 P〗_(m ) : C_n^((2))]graphs and their proper d- lucky numbers are obtained.